APLIKASI RESERVASI TRAVEL MENGGUNAKAN PAYMENT GATEWAY DI UD LAJU JAYA TOUR AND TRAVEL BERBASIS WEB - Aprilian Ihza Abin Nizar (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
The rapid development of information technology in the current era of modernization has changed many humanlifestyles in all fields, both private and government agencies to the general public. Laju Jaya Tour & Travel providestransportation services that are known to be on time in the departure schedule. The problem faced is the lack of departureschedule information which makes consumers do not know the departure schedule. Even ordering tickets is not efficientbecause they still use the recording process. To solve this problem, a Travel Reservation web was created to make it easierfor customers to order tickets. Data collection was carried out by conducting interviews directly related to the object understudy and reviewing the necessary needs. This system was built using the JavaScript programming language and MERNStack technology, namely the Mysql database, the ExpressJs framework on the backend, ReactJs on the frontend and NodeJs. In making this information system using the waterfall method. This system has been tested using blackbox testing to getthe expected results and the system is feasible to use. The system is expected to be able to assist in managing travelreservation data where as long as ticket ordering is still done manually. This system has limited features so that it can bedeveloped to make it even better and is expected to have high performance in terms of its software developmentinfrastructure, so it needs regular development.